“Beyond the immediacy”: Axiological experiences of engineering students during the “new normal” - Mtonjeni, Thembinkosi; Sefalane-Nkohla , Puleng (Journal for Language Teaching, 2023)
Writing Centre Intervention (WCI) in the faculty is a pedagogical resource to facilitate the students’ academic literacy development. In our universities, literacy development focuses mainly on enhancing students’ cognitive, linguistic and epistemological experiences – with little attention given to the psycho-social and ontological dimensions of learning, especially in the science related fields such as electrical engineering. This paper draws on Academic Literacies, Systemic Functional Linguistics and Legitimation Code Theory to study the axiological experiences of first year electrical engineering students at the Cape Peninsula University of Technology (CPUT). The participants for the study were drawn from the students who participated in the WCI, a collaborative, interdisciplinary project designed to help electrical engineering first year students to develop “soft skills” alongside technical-scientific knowledge. Since the workshops were facilitated under Covid-19 lock down restrictions, blended learning was employed. Interviews were conducted via MS Teams. The participants’ utterances demonstrated a mixed bag of emotions, an ideological shift, albeit at different degrees, and strong attitudes toward the learning of the engineering “soft skills”. Therefore, the study calls for a pedagogy of wholeness wherein the epistemological, spiritual, axiological and ontological dimensions of learning are attended to and activated in order to move students’ perceptions “beyond the immediacy” of the current experience.